(untitled) (Scripta Medica, 2020)
In Issues 1 and 2 the scientific journal Scripta Medica devoted a total of six articles to the aetiological, epidemiological and clinial aspects of serious acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the disease caused by this virus - coronavirus disease 2019 (COVID-19). The present Issue 2 also contains an obituary on the occasion of demise of Professor Folke Sjo Sjökvist, one of the founding fathers of Clinical pharmacology as a discipline and several other articles from the fields of quality assurance in healthcare, experimental and clinical medicine.